Mustafa: a Naib in Action in the Kaza of Cos in the first half of the eighteenth century - Ursinus, Michael (Turcica, 2020)
The Naib Mustafa was charged by successive Cadis of Kos with looking after the island of Patmos for more than 30 years, although he could possibly have acted on his own initiative in some instances. About half a dozen of hüccets sporting his 'signature', distinctive handwriting and seal imprint, all from the Ottoman holdings of St John monastery on Patmos, form the basis of the investigation, complemented by documents composed in Greek from some of the Greek metochia files (which now form part of the monastic archive of Patmos) which also show his seal mark, dating from between 1709 and 1746. Mustafa who, given his writing style and mode of expression, most probably was a Greek (convert), constitutes a hitherto little known example of a regional 'specialist' naib, 'officiating' on Patmos and, occasionally, on another island (such as Kalymnos) along the sea route from Kos to Patmos. The involvements of Mustafa in the intricacies of the internal 'balance of power' in the island of Patmos suggest that he was an important player because of his insider knowledge as a 'regional specialist' practicing his skills over many decades, but particularly as a Greek convert to Islam whose intimate knowledge of local society and the Greek language paired with an official position in the Ottoman judicial system as a naib made him a man the contending parties in Patmos evidently could not do without.